Pengelolaan Pajak Kendaraan Bermotor Provinsi Bali Tahun 2021-2022 Berdasaran Peraturan Daerah Provinsi Bali Nomor 9 Tahun 2019 Tentang Pajak Daerah: Management of Vehicle Tax in Bali 2021-2022 Based on Regional Regulation Number 9 of 2019 on Local Tax - Salsabilla Saeed Hassan; Muhammad Imam Nasef (Faculty of Law, Universitas Trisakti, 2025)
The authority of the Bali Provincial Government in managing motor vehicle tax as one of the largest sources of local tax revenue. The problem is how the authority of the Bali Provincial Government in managing Regional Original Revenue (PAD) based on Regional Regulation Number 9 of 2019 and how the contribution of the tourism sector to Regional Original Revenue in Bali Province. This research uses normative juridical methods, descriptive in nature, using secondary data which is analyzed qualitatively and drawing conclusions using the deductive method. The result and the conclusion of this study is that the Regional Government is authorized to manage Regional Original Revenue in the tourism sector in accordance with Regional Regulation Number 9 of 2019 concerning the Third Amendment to Regional Regulation Number 1 of 2011 concerning Regional Taxes. It has been regulated regarding the collection rates and sanctions that must be applied by the Regional Government. Revenue from vehicle tax in 2022 has decreased by only 43.77% from the previous year which could reach 50% of Regional Original Revenue in Bali Province. From this amount, it is also explained about the factors and obstacles in collecting motor vehicle tax in Bali Province